Avoiding laboratory pitfalls in infectious diseases. Issue 949 (10th November 2004) - Lo, T S; Smego, R A
Abstract : In today's medical care environment, clinicians are challenged to order clinically relevant, cost effective laboratory tests and antibiotic therapy. Together, physicians and laboratories must have guidelines and strategies that can provide quality patient care, while minimising costs and preventing further emergence of antimicrobial drug resistance. Five clinical vignettes that demonstrate these principles are presented.